No alto da colina e na sombra da história: educação de meninas e meninos no orfanato Cristóvão Colombo (1895-1953) - Lopes, Idileini Corrêa (2015)
The present study was determined in order to weave the plot of the host institutions for underprivileged children that performed not only a care work, but also an educational one, supported by didactic-pedagogical processes developed in the country in the late 19th and early 20th centuries. We had as main focus of our analysis the Orfanato Cristóvão Colombo, located in São Paulo city, where students received an instruction according to current standards of the public instructions and based on the principles of the Roman Catholic religion, in addition to the instruction required for the practical life, in the case of girls, and professionalization, in the case of boys. The problem that instigated us was unveil if the didactic-pedagogical practices and processes experienced at the Orfanato Cristóvão Colombo corresponded to culture and to the then-current education or if they had specificities meeting self-interests of the institution. We started from several hypotheses, among them finding out if the educational process adopted by the Orfanato Cristóvão Colombo was a reflection of a society panorama towards excluded children at that time, or even if it countersigned the current educational values, enabling the underprivileged children to be inserted in the society. For the analysis, we delimited the year 1895, date of Orphanage foundation, and we finalized in the year 1953, when the orphanage was renamed Instituto Cristóvão Colombo, outsourcing the vocational education. To find answers to our questions, we conducted a literature search, in order to rescue some historical gaps on the foundation of the Orfanato Cristóvão Colombo and on the pastoral and assistance project prepared by Don João Batista Scalabrini. The search for data, information and photographs, which helped us to elucidate the theme, led us to carry out an exploratory research in the Archive of the Instituto Cristóvão Colombo, in the Archive of the Cúria Metropolitana de São Paulo, among others. The Thematic Oral History has also employed as a methodological resource, carrying out interviews with former students of the Orfanato Cristóvão Colombo, another methodological resource was the historical and dialectical approach. The importance of the study of Educational Institutions is justified not only by preserving the memory, but also by understanding the education history as a whole. We concluded that the primary education followed the parameters of the São Paulo public school, adopting both the didactic-pedagogic method, and the materials such as books and booklets for both male and female sections. As regards the vocational education, we realized that for the boys it were willing more elaborated workshops such as blacksmithing, carpentry, locksmiths and typography. For girls there wasn´t this investment. We noted only the presence of some sewing machines to turn the space into a place of skilled labor, short of a vocational school structure. We hope that this work will contribute to the preservation of the History of the Orfanato Cristóvão Colombo and the History of Educational Institutions.